THE CONCEPTUAL MAP SOLUTION TO THE PARADOX OF CONCEPTUAL ANALYSIS - Terence Rajivan Edward (IJRDO- Journal of Educational Research, 2023)
Why do a conceptual analysis on a word that we already know how to use? Marilyn Strathern provides some information on garden cities and suburbs which suggests a novel solution to me.